Glucosamine Induces Activated T Cell Apoptosis Through Reduced T Cell Receptor. (11th July 2013) - Chen, N.‐H.; Cheong, K. A.; Kim, C.‐H.; Noh, M.; Lee, A.‐Y.
Abstract Glucosamine (GlcN), like N‐acetylglucosamine (GlcNAc), is salvaged into the hexosamine pathway and is converted to UDP‐GlcNAc. Golgi N‐glycan branching enzymes produce N‐glycans, using UDP‐GlcNAc as a substrate, which attach to the T cell receptor (TCR) and cytotoxic T‐lymphocyte antigen‐4 (CTLA‐4). These findings suggest that GlcN exerts the immunoregulation through TCR signalling, which could be involved not only in cytokine production but also activated T cell apoptosis. In fact, a preliminary study showed that GlcN reduced the number of CD3+ T cells of NC/Nga mice with AD‐like skin lesions. Therefore, whether apoptosis of T cells would be one of the potential molecular mechanisms of GlcN‐induced immunosuppression was investigated. Cultured human primary along with Jurkat T cells and purified T cells from NC/Nga mice with or without Df‐induced AD‐like skin lesion were used for the study. Glucosamine treatment increased the number of T cells expressing β1, 6GlcNAc‐branched N‐glycans, with reduced ZAP‐70 phosphorylation and enhanced CTLA‐4 expression. Glucosamine treatment reduced the number of activated T cells from both the human primary and Jurkat cells and the dermatitis‐induced mice. The expression of FasL and activated caspases, particularly caspase‐3, was increased, whereas the phosphorylation of PI3K, Akt and NF‐κB was decreased by GlcN treatment. Therefore, in addition to down‐regulating TCR signalling and promoting CTLA‐4 expression, GlcN may also suppress T cell function by enhancing apoptosis of activated T cells, through both extrinsic and intrinsic apoptotic signalling pathways, which were regulated by the inhibition of PI3K/Akt and NF‐κB phosphorylation.